An analysis of adjacency influence on verb number in English - Alhiti, Sheren Khalid Abdul Razzaq (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
This study makes a foray into the study of verb number in complex noun phrases. More specifically, the aim is to find out the influence adjacent and distal nouns have in determining verb number. The secondary aim is to find out if explanations are available for any pragmatic deployment of verb number. In carrying out this study, the researcher employed the meaning-based framework proposed by Reid (1991) to examine the verb phrases present in native speakers' academic writing - academic books and journal articles. The data for this study included texts in which there were two nouns in the subject noun phrase followed by one verb. The data were culled from seven books and five journal articles. The aim was to check the noun position and its influence over the choice of verb number. The study revealed that both distal and adjacent nouns have an impact on verb number deployment. On a relative scale, however, verb number is strongly affected by distal noun rather than adjacent noun. It was also found that distal noun influence creates a pattern that supports SVA rule while adjacent noun influence does not form a particular pattern and differ according to the messages conveyed by the encoder. It appears that native speakers dispense with the SVA rule to convey certain messages because messages are infinite but language forms provided by the rule are finite; thus the needs of language users accede to the tools available. The meaning-based approach used in this study helped in showing clearly the deployment of verb use, a result of the creativity of language users. It has to be stated that a meaning-based second language teaching approach would help to raise students' awareness of this grammatical feature.